Salivary flow rate response to stimulation with 2% citric acid in patients with xerostomia - Saavedra, Juan Aitken; Muñoz, Rodrigo Ponce; Alcayaga, Gonzalo Rojas; Tarquinio, Sandra Chaves; da-Silva, Karine Duarte; Ramires, Ricardo Fernandez; Bozo, Irene Morales (Journal of Oral Diagnosis, 2018)
Objective: Xerostomia is the subjective sensation of dry mouth and it can be an indicator of hyposalivation what would have clinical consequences like increased risk of the development of oral diseases. For this reason, the stimulation of salivary flow with organic acids, such as citric acid, must be considered as a treatment strategy for xerostomic patients with hyposalivation. This study aimed to determine the salivary responses of patients with xerostomia to stimulation on the tongue with 2% citric acid. Material and Methods: This study recruited 62 patients with xerostomia. The differences in salivary flow rate (SFR), pH, and buffer capacity values were determined before and after 1, 2, 3, 5, 7, 9, 11, 13, or 15 min of stimulation on the tongue with 2% citric acid. Results: Among the recruited patients, 92% were women and 53% had hyposalivation. The average age of the recruited patients was 55 years. The mean basal SFR value was 0.282 ml/min (DS 0.305). SFR (p=0.001) increased and pH (p=0.000) and buffering capacity (p=0.000) decreased at 1 min poststimulation relative their basal values. The values of the three parameters stabilized at 2 min poststimulation and remained constant until the end of the measurement period. Conclusion: Citric acid could be used to stimulate salivary flow in xerostomic patients with hyposalivation maintaining salivary pH values and buffering capacity within an acceptable range. However, to be considered a possible therapy for this kind of patients, it is still necessary to perform more studies.